Trimethoprim–sulphamethoxazole does not affect the pharmacokinetics of sirolimus in renal transplant recipients - Böttiger, Ylva (Blackwell Science Inc, 2005)
AIMS: The influence of the trimethoprim–sulphamethoxazole combination on the steady-state pharmacokinetics of sirolimus, a potent macrocyclic immunosuppressant, was studied in renal transplant recipients. METHODS: Fifteen kidney transplant recipients were treated with sirolimus 8–23 mg m(−2) in combination with azathioprine and prednisolone from the day of transplantation. Whole blood sirolimus AUC and C(max) were determined on days 6 and 7 after transplantation. On day 7, sirolimus was coadministered with the first dose of trimethoprim (80 mg) and sulphamethoxazole (400 mg). RESULTS: On day 6, the mean (95% confidence interval) whole blood sirolimus AUC((0–24 h)) was 1040 (846, 1234) ng ml(−1) and mean C(max) was 109 (88, 129) ng ml(−1). Corresponding values on day 7 were AUC((0–24 h)) 1060 (826, 1293) ng ml(−1) and C(max) mean 107 (87, 127) ng ml(−1). The mean difference in the dose-corrected AUC((0–24 h)) was 0.40% (−9.4, +10). CONCLUSIONS: A single dose of trimethoprim–sulphamethoxazole does not affect the pharmacokinetics of sirolimus in renal transplant patients.